Cardiovascular Autonomic Response to Amlodipine in Primary Hypertension. (25th June 2012) - Radjab, Youssouf; Aboudrar, Souad; Milouk, Fatima Zahra; Rkain, Hanan; EL Bakkali, Mustapha; Dakka, Taoufiq; Coghlan, Leslie; Benjelloun, Halima
Abstract : Sympathetic hyperactivity may be involved in primary hypertension. The purpose of this study was to evaluate both sympathetic and vagal activity responses in patients receiving amlodipine as antihypertensive agent. Patients and Methods . This prospective study included a group of primary hypertensive patients (N = 32, mean age 54.6 ± 7.6 years). The cardiovascular autonomic tests performed in this group, before and after 3 months of daily oral administration of amlodipine, included deep breathing, hand-grip, and mental stress tests. Statistical analysis was done using the Student's t -test. Results . Cardiovascular autonomic reflexes responses before and after 3 months of amlodipine oral administration were as follows: the mental stress test stimulation method produced a central alpha adrenergic response of 23.9 ± 8.7 % versus 11.2 ± 2.0 % (P < 0.05 ), a central beta sympathetic response of 16.7 ± 9.2 % versus 10.4 ± 1.3 % (P < 0.05 ), a blood pressure increase in response to hand grip test of 20.5 ± 7.3 % versus 10.7 ± 2.4 % (P < 0.05 ), vagal response to deep breathing test was 21.2 ± 6.5 % versus 30.8 ± 2.9 %, (P < 0.05 ). Conclusion . The results attest that amlodipine may have an anti-sympathetic effect.